Efektivitas BI7DRR dalam Kerangka Mekanisme Transmisi Kebijakan Moneter untuk Pengendalian Inflasi - MG Westri Kekalih Susilowati; Retno Yustini Wahyuningdyah (Soegijapranata Catholic University, 2018)
Bank Indonesia launched BI 7DRR replacing the BI Rate in order for banks to withdraw their reserves in 7 days' tenure. Thus, banks do not have to wait for 365 days to withdraw their reserves. This study aimed to determine the effectiveness of BI 7DRR in controlling inflation. By using Partial Least Square model estimation (PLS) approach to generate multiple relationships model between factors to the schemes, this research found that on BI Rate scheme BI Rate has a negative effect on credit disbursement and positive effect on interest rate, expectation has negative effect on inflation, consumption has positive effect to GDP, exchange rate has negative effect to export, GDP has negative effect to Inflation, and credit has a positive effect on consumption. Meanwhile, on BI7DRR estimated model shows that BI7DRR has negative effect on expectation and exchange rate but has positive effect on interest rate, exchange rate has positive effect on export, and interest rate has negative effect on investment and credit disbursement. This research also found that the paired samples T Test indicates a significant difference between two mean of inflation according to the two schemes. Therefore, it can be concluded that BI7DRR effective to control the inflation